The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/bjh.14771
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 receptor blockade as new possible therapeutic approach in multiple myeloma

Abstract: New effective treatments are needed to improve outcomes for multiple myeloma (MM) patients. Receptors with restricted expression on plasma cells (PCs) represent attractive new therapeutic targets. The endothelin-1 (EDN1) axis, consisting of EDN1 acting through EDN-receptor A (EDNRA) and B (EDNRB), was previously shown to be overexpressed in several tumours, including MM. However, there is incomplete understanding of how EDN1 axis regulates MM growth and response to therapy. Besides EDNRA, the majority of MM ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…Vaiou et al () previously demonstrated a protective role for EDNRB in bortezomib‐treated NCI‐H929 and RPMI‐8226 cells, showing that the MAPK pathway was the predominant signalling pathway involved in EDN1/EDNRB‐induced bortezomib resistance. In our paper (Russignan et al , ), a synergistic effect of bosentan and bortezomib in both U266 and RPMI‐8226 cells was demonstrated. Interestingly, new data (see Fig.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Vaiou et al () previously demonstrated a protective role for EDNRB in bortezomib‐treated NCI‐H929 and RPMI‐8226 cells, showing that the MAPK pathway was the predominant signalling pathway involved in EDN1/EDNRB‐induced bortezomib resistance. In our paper (Russignan et al , ), a synergistic effect of bosentan and bortezomib in both U266 and RPMI‐8226 cells was demonstrated. Interestingly, new data (see Fig.…”
supporting
confidence: 60%
“…We thank Dr. Schäfer and colleagues for their interest in our study (Russignan et al , ) and to better reflect our current understanding of the role of the endothelin‐1 (EDN1) axis as a therapeutic target in multiple myeloma (MM). We reply to the criticisms they raised about our work by providing further findings that envision the possibility of interfering with EDN1 receptor activity in exploring a novel therapeutic strategy for MM patients.…”
mentioning
confidence: 99%
“…Recently, it has been observed an abnormal expression of endothelin receptor type B (EDNRB) in hepatocellular carcinoma and confirmed its potential clinical significance (Zhang et al 2019). Thus, endothelin-1 receptor blockade is new possible therapeutic approach in multiple myeloma, because the majority of multiple myeloma cell lines and primary malignant plasma cells express high levels of EDNRA and EDNRB and release EDN1 (Russignan et al 2017).…”
mentioning
confidence: 94%
“…Most recently, experimental data reported by Russignan et al () underlined previous data. Their data again suggests an important role of the endothelin axis in multiple myeloma, which can be functionally blocked by bosentan, an EDNRA and EDNRB antagonist (Russignan et al , ).…”
mentioning
confidence: 54%